-3x+17=-4x+16

Simple and best practice solution for -3x+17=-4x+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+17=-4x+16 equation:


Simplifying
-3x + 17 = -4x + 16

Reorder the terms:
17 + -3x = -4x + 16

Reorder the terms:
17 + -3x = 16 + -4x

Solving
17 + -3x = 16 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
17 + -3x + 4x = 16 + -4x + 4x

Combine like terms: -3x + 4x = 1x
17 + 1x = 16 + -4x + 4x

Combine like terms: -4x + 4x = 0
17 + 1x = 16 + 0
17 + 1x = 16

Add '-17' to each side of the equation.
17 + -17 + 1x = 16 + -17

Combine like terms: 17 + -17 = 0
0 + 1x = 16 + -17
1x = 16 + -17

Combine like terms: 16 + -17 = -1
1x = -1

Divide each side by '1'.
x = -1

Simplifying
x = -1

See similar equations:

| 6+5j=33 | | p^5=1-2p^3 | | 14-5p=-3p-2 | | -5x+6=-4x+-7 | | 55x=110 | | asd=5 | | 2m^2+13m=24 | | 6x^2-10x-10=0 | | 26x-11-14x=3(4x-5)+4 | | 4x-29=-1x+-4 | | 14+5x=40 | | 6x-54=4x-20 | | -17x^2+13x+13=0 | | b^2+10b= | | 0=-17x^2+13x+13 | | -7=4+x/5 | | 92x+5=32x+17 | | 2x+2=4x-18 | | 23x=240 | | 11x+6y=18 | | 7+16x=80 | | 109-7x=20x+19 | | 2(-3x+3)-6x=-6 | | y/5+4=40.5 | | 23x=80 | | 9z-11=-65+3z | | (2y-5)(3y+7)= | | 0=-16t+vt+c | | 9z-11=65+3z | | (3x-2)(3x+2)=9x^2-18x+9-6(4-x)+12x | | x(12-104)=x(4-8) | | 2(-5x-7)+10x=-8 |

Equations solver categories